Lost and Found: An Application to Search and Find Lost Items - Romadhona, Yasinta; Sjahrunnisa, Anita; Yuhana, Umi Laili (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2023)
Carrying personal items is a must for everyone, especially to the campus area. It can cause people to lose things, and many lost or found items pile up without the owners. However, to communicate this information, only broadcasts were implemented through chain messages on social media which were considered less effective. Based on these problems, a website-based information system is proposed to assist in managing reports of lost and found items and transactions between finders and searchers of the items. This system has three main functions: inserting data on lost or found items, deleting items that have been returned to their owners, and making claims for items by exchanging messages to each user’s account. This system is built using PHP, HTML, CSS, JavaScript and is referred to the waterfall model. This information system can be accessed through a web browser on a device, so there is no need to install many applications because a browser is installed by default there. The purpose of this study is to measure the usability scale. This information system is expected to facilitate interaction for searchers and finders of the items and be a convenient alternative so that cases of lost items in the campus area can be handled effectively and efficiently. Evaluation of the system using the System Usability Scale (SUS) has a score of 77 which means it is acceptable or feasible.